Pendidikan Literasi Terintegrasi Keislaman Menggunakan Pendekatan High Order Thinking Skill (HOTS) Dalam Menumbuhkan Kemandirian Belajar - Santi Laura Pelenusa; Darni; La Ode Bangungsi Ali (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Literacy is currently being researched in the world of education. Islamic integrated literacy education makes students able to understand literacy correctly according to the socio-cultural and religious context. Literacy is an activity that involves HOTS. Literacy also has a close relationship with independent learning. This research is a descriptive qualitative research that aims to describe integrated Islamic literacy education using the HOTS approach in fostering independent learning. The subjects in this study were 17 students of the Ambon IAIN Mathematics Education Study Program. This research was conducted at the Mathematics Education Study Program at IAIN Ambon for 2 weeks. Data collection techniques used are tests and questionnaires. The test given to students aims to find out how students' literacy skills are after obtaining reading literacy education and Islamic integrated numeracy literacy. Questionnaires are given to determine student learning independence. The instruments in this study were test questions and questionnaires through the Google Form facility. The test carried out was a multiple choice test which contained 10 questions on integrated Islamic reading literacy and 10 questions on integrated Islamic numeracy literacy. The questionnaire contains questions about learning independence which consists of aspects of self-confidence, discipline, initiative, motivation, and responsibility. The test data analysis technique is giving a score ranging from 0 to 100. The questionnaire data analysis technique is analyzing the percentage of student responses consisting of strongly agree, agree, disagree, and strongly disagree. The results of the study show that the ability to integrate Islamic literacy using the HOTS approach to students is very good. The reading literacy ability of students is higher than the numeracy literacy ability. The independence of student learning through integrated Islamic literacy education using the HOTS approach is very good. Most students strongly agree that their learning independence can be grown through integrated Islamic literacy education using the HOTS approach. Keywords: Literacy; Literacy Education; Islamic Integrated Education; HOTS; Independent Learning.